The Politics of Remediation : Institutional and Student Needs in Higher Education - Soliday, Mary (Book collections on Project MUSE., 2002)
"The Politics of Remediation examines the history and politics of remediation in higher education, and calls into question traditional notions of remedial instruction. Soliday traces the history of remedial college English from the late nineteenth century to the 1990s, providing a framework for a field that has traditionally focused on the present. Historically, writing programs have taken on the role of mediator: offering democratic access to growing numbers of students while protecting an institution's selectivity; and increasing enrollments while also promoting the research and development that attracts corporate, state, and federal funding."--Jacket.